Pengendalian Kualitas dalam Perencanaan Produksi Menggunakan Alat Bantu Seven Tools di Perusahaan Konstruksi - Hermawan, Fachrezi Rizki; Safariyani, Eva (Fakultas Teknik Universitas Tulang Bawang, 2024)
Increasingly fierce competition in the business world encourages companies to further develop ideas for effective and efficient ways to achieve predetermined goals. Many factors influence the success of achieving company goals. One of the most important forces that supports the achievement of company goals and increases company growth in the market is quality or quality score. Product or service quality control is critical to ensuring customer satisfaction and business success. One of the quality control tools is